Utility of Peak Inspiratory Flow in Managing Subglottic Stenosis. (June 2015) - Tasche, Kendall K.; Bayan, Semirra; Schularick, Nathan M.; Wilson, Jeff; Hoffman, Henry T.
Objectives: To identify the utility of peak inspiratory flow (PIF) in the assessment and management of subglottic stenosis through correlation of clinical presentation with PIF. Study Design: Case report. Methods: Review of the clinical course of a 31-year-old woman with the diagnosis of granulomatosis with polyangiitis. Repeated PIF measurements at clinic visits were obtained over a 30-month follow-up. Results: Twenty-seven PIF measurements were obtained at 31 otolaryngology clinic visits. Correlations were identified between low PIF measurements with the clinical symptom shortness of breath (2.04 ± 0.38 L/s, n = 10), clinically recorded stridor at rest (1.64 ± 0.41 L/s, n = 3), and urgent operative intervention (1.60 ± 0.23 L/s, n = 5). Correlations were identified between high PIF measurement with patient report of normal breathing (3.07 ± 0.35 L/s, n = 16) and clinical observation of absence of stridor at rest (2.81 ± 0.32 L/s, n = 23). There was a statistically significant difference in the patient's PIF values with patient-documented shortness of breath vs no shortness of breath ( P = .001) and clinician-noted stridor vs no stridor ( P = .017). Conclusion: Peak inspiratory flow measurements correlate with degree of airway compromise and are helpful to monitor the degree of airway obstruction and document response to treatment.